Cultivando Política Pública, colhendo autonomia: análise da participação das mulheres agricultoras da região metropolitana de Santarém - PA no Programa de Aquisição de Alimentos - PAA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The present study discusses the relationship between female autonomy and the institutional food purchasing market, with the objective of analyzing the implications that the insertion in the institutional markets, specifically in the Programa de Aquisição de Alimentos (PAA), generates in the economic autonomy of women farmers who are beneficiaries of the program. This work is based on bibliographical and field research, with semi-structured interviews with the coordination of PAA and the women farmers living in the Metropolitan Region of Santarém-PA. The quantitative approach was used to describe the socioeconomic profile of women farmers; qualitative research to deepen and understand the subjective aspects concerning the universe of the study. As a result, the PAA of Santarém was constituted from the articulation of several social actors and the municipal management of Santarém, producing institutional arrangements with a focus on encouraging farmers. The participation of women farmers in the program led to the achievement of economic autonomy, increase of income and overcoming the condition of subordination in relation to the spouses. Opportunized access to actions focused on minimizing the gender inequalities that historically permeate the rural environment, especially in productive spaces. But because it is an ongoing process that promotes the reorganization of roles and changes in the power relations established in the family nucleus, it is necessary to enforce the quota established for women, in order to implement actions for the visibility of rural women, in fact contributing for their emancipation. It is necessary to monitor the implementation of the PAA, its usefulness and effectiveness, through further in-depth studies, with the aim of broadening the debates on the issue of women farmers' autonomy, insertion in productive work and marketing context. As well as socializing with the interested sectors, in order to subsidize the development of Public Policies focused on promoting the economic autonomy of women farmers.
Keywords: Mercado Institucional; Programa de Aquisição de Alimentos; Autonomia econômica; Gênero; CNPQ::CIÊNCIAS HUMAMANS; POLÍTICAS PÚBLICAS E DESENVOLVIMENTO REGIONAL